Correlation of TNF 308 Polymorphisms and Susceptibility to Respiratory Disease - Shaimaa H. Al -Dulaimi; Adel M. Rabee (Institute of Medico-legal Publications Pvt Ltd, 2021)
l Both genotypic and allelic frequency of rs1800629 show in significant difference between concrete laborers and healthy controls. Nevertheless the frequency of A allele was insignificantly increase in laborers (20%) than in controls (14%) (P = 0.077; OR = 1.61; 95% CI = 0.72 to 3.58). After analyzing the relationship between TNFaserum levels of laborers and genotype of TNF-a-308G/A, we detected the laborers that carrying the GA and AA genotypes had significantly higher levels of TNFacompared to GG genotype carriers of rs1800629 ( P< 0.01). Consequently, our information proposed that TNF-a-308G/A variation was linked to risk of respiratory disease in concrete laborers. Moreover, we also identified TNF-a-308 A allele was the risk factor for concrete laborers in Iraqi population.